Exact Boundary Controllability on a Planar Tree-Like Network of Vibrating Strings with Dynamical Boundary Conditions (Journal of Mathematical Study, 2018)
This paper concerns a planar tree-like network of vibrating strings withpoint masses at the nodes. We use a constructive method with modular structure to getthe ‘one-sided’ exact boundary controllability for this system with dynamical boundaryconditions. Moreover, by constructing the ‘longest’ chain-like subnetwork and its ‘midpoint’, we divide the whole tree-like network into two tree-like sub-networks, andprove the ‘two-sided’ exact boundary controllability.